Recent progress in chemical approaches for the development of novel neuraminidase inhibitors. Issue 3 (6th January 2021) - Mahal, Ahmed; Duan, Meitao; Zinad, Dhafer S.; Mohapatra, Ranjan K.; Obaidullah, Ahmad J.; Wei, Xiaoyi; Pradhan, Manoj K.; Das, Debadutta; Kandi, Venkataramana; Zinad, Hany S.; Zhu, Quanhong
Abstract : Influenza virus is the main cause of an infectious disease called influenza affecting the respiratory system including the throat, nose and lungs. Abstract : Influenza virus is the main cause of an infectious disease called influenza affecting the respiratory system including the throat, nose and lungs. Neuraminidase inhibitors are reagents used to block the enzyme called neuraminidase to prevent the influenza infection from spreading. Neuraminidase inhibitors are widely used in the treatment of influenza infection, but still there is a need to develop more potent agents for the more effective treatment of influenza. Complications of the influenza disease lead to death, and one of these complications is drug resistance; hence, there is an urgent need to develop more effective agents. This review focuses on the recent advances in chemical synthesis pathways used for the development of new neuraminidase agents along with the medicinal aspects of chemically modified molecules, including the structure–activity relationship, which provides further rational designs of more active small molecules.